HOW TO DESCRIBE THE RESULTS OF OBSERVATIONAL EPIDEMIOLOGICAL STUDIES - S. A. Shal'nova; A. D. Deev (Столичная издательская компания, 2016)
Principles and fundamentals of proper presentation of observational epidemiological study results are focused. Principles of observational study publication developed by expert epidemiologists (STROBE statement) are explained in detail.